Inactivation of Inulinase and Marination of High-Quality Jerusalem Artichoke (Helianthus tuberosus L.) Pickles With Screened Dominant Strains - Zhang, Li; Liu, Wei; Ji, Jiahong; Deng, Lina; Feng, Qian; Shi, Wujian; Gao, Jian (Frontiers in Bioengineering and Biotechnology, 2021)
Freshly harvested Jerusalem artichoke tubers contain inulinase, an enzyme that requires inactivation, because of its ability to hydrolysis inulin into fructose, which can be consumed by microorganism during marination. As the traditional pickling process takes 6 months, and involves the addition of a large amount of salt (18–20%), this production strategy is uneconomical and increases the nitrite intake. Additionally, miscellaneous bacteria produced during pickling affect the product taste. In this study, the enzyme inactivation effects of NaCl, NaHCO3, and ultrasound were evaluated. NaHCO3 treatment results in the highest degree of enzyme inactivation; however, the quality and flavor of the obtained Jerusalem artichoke pickles were not ideal. The Jerusalem artichoke pickles in which the enzymes were inactivated using a combination of NaCl and ultrasound exhibited better flavor than those exposed to NaHCO3; further, this combination reduced the inulinase activity of the Jerusalem artichokes to 2.50 U/mL, and maintained the inulin content at 61.22%. The strains LS3 and YS2, identified as Enterococcus faecalis and the salt-tolerant yeast Meyerozyma guilliermondii, respectively, were the dominant microorganisms isolated from the pickle juice. Jerusalem artichokes with inactivated inulinase were pickled with microbial powder, separated, purified, and dried to remove the natural Jerusalem artichoke sauce. This process shortened the fermentation cycle and improved product quality.